Deciphering midbrain mechanisms underlying prepulse inhibition of startle. (February 2020) - Fulcher, Niveen; Azzopardi, Erin; De Oliveira, Cleusa; Hudson, Roger; Schormans, Ashley L.; Zaman, Tariq; Allman, Brian L.; Laviolette, Steven R.; Schmid, Susanne
Highlights: DREADD inhibition in PPTg and/or adjacent structure disrupts PPI upon i.p. CNO. Startle latency increases following DREADD-induced inhibition of PPTg neurons. Transient inhibition of PPTg cholinergic neurons does not influence PPI. In vivo and in vitro electrophysiology verify DREADD inhibition upon i.p. CNO. Chemogenetic inhibition of all PPTg neurons or ACh neurons specifically blocks CPP. Abstract: Prepulse inhibition (PPI) is an operational measure of sensorimotor gating. Deficits of PPI are a hallmark of schizophrenia and associated with several other psychiatric illnesses such as e.g. autism spectrum disorder, yet the mechanisms underlying PPI are still not fully understood. There is growing evidence contradicting the long-standing hypothesis that PPI is mediated by a short feed-forward midbrain circuitry including inhibitory cholinergic projections from the pedunculopontine tegmental nucleus (PPTg) to the startle pathway. Here, we employed a chemogenetic approach to explore the involvement of the PPTg in general, and cholinergic neurons specifically, in PPI. Activation of inhibitory DREADDs (designer receptors exclusively activated by designer drugs) in the PPTg by systemic administration of clozapine-N-oxide (CNO) disrupted PPI, confirming the involvement of the PPTg in PPI. In contrast, chemogenetic inhibition of specifically cholinergic PPTg neurons had no effect on PPI, but inhibited morphine-induced conditioned place preference (CPP) in the same animals, showing that the DREADDs were effective in modulating behavior. These findings support a functional role of the PPTg and/or neighboring structures in PPI in accordance with previous lesion studies, but also provide strong evidence against the hypothesis that specifically cholinergic PPTg neurons are involved in mediating PPI, implicating rather non-cholinergic midbrain neurons.